VD_FINDINFO Jug / 2023 / 476 vom 2. März 2023 - VD Tribunal cantonal (2023)
DÉTENTION D'ARMES, CONFISCATIONDROIT PÉNAL, INDEMNITÉEN GÉNÉRAL, INTENTION | 12 al. 2 CP, 69 CP, 33 al. 1 let. a LArm, 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)